Causation, permission, and transfer : argument realisation in GET, TAKE, PUT, GIVE and LET verbs - Nolan, Brian, 1952-; Rawoens, Gudrun, 1969-; Diedrichsen, Elke (Studies in language companion series, 2015)
This chapter aims to study the prepositional marking and the postpositional marking of the recipient in the Persian non-canonical ditransitive alignments, which are associated respectively with a particular role that the recipient as topic or exhaustive focus plays in the information-structural representation of the benefactive event. I will argue that overriding of the theme and recipient by each other with respect to topicality, grammatically achieved by utilizing two distinct operations including preposing and left-dislocation, determines the intended grammatical marking of the recipient. M.